3-D magnetotelluric inversion for geothermal exploration in Socompa volcanic zone, NW Argentina - Guevara, Liliana Mariela (2018)
The Socompa volcano lies in the arid core of the Puna region. It is a stratovolcano whose summit reaches 6,051 m high and it is located between the limit of the Antofagasta region, Chile and the Province of Salta, Argentina. The volcano is located in a sterile environment, and the diversity and abundance of life that has been documented in the region is explained through a geothermal system revealed in the form of fumaroles and hot springs of stable temperatures. These manifestations suggest the importance of a magnetotelluric (MT) research to study a potential geothermal field that has not been explored. The MT method has been widely used in geothermal exploration. In December 2017, we carried out the first survey in the region. The present work is oriented to determine the top of the layer that could be the reservoir of the geothermal system. According to the literature, thermal manifestations are located in the Socompa Lagoon and in Quebrada del Agua fault. The survey consisted in 34 MT stations that covered the area. A 3D inversion was performed employing the ModEM code using a frequency range from 1 to 1000 Hz. The results showed a highly conductive layer at approximately 450 m depth.